2010
DOI: 10.1111/j.1365-2427.2010.02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐native fishes and climate change: predicting species responses to warming temperatures in a temperate region

Abstract: Summary 1. Temperate regions with fish communities dominated by cold‐water species (physiological optima <20 °C) are vulnerable to the effects of warming temperatures caused by climate change, including displacement by non‐native cool‐water (physiological optima 20–28 °C) and warm‐water fishes (physiological optima >28 °C) that are able to establish and invade as the thermal constraints on the expression of their life history traits diminish. 2. England and Wales is a temperate region into which at least 38 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(185 citation statements)
references
References 53 publications
5
179
0
1
Order By: Relevance
“…By contrast, the following non-native fishes were omitted from the study to avoid confounding issues with their heavy use in aquaculture would have potentially exposed them to a range of anti-parasite treatments: common carp Cyprinus carpio, goldfish Carassius auratus, rainbow trout Oncorhynchus mykiss and ide Leuciscus idus. Indeed, should any of these species be sampled in the wild in England and Wales then there is high probability they originated from a fish-farm as there are, for example, few naturally recruiting populations of C. carpio and O. mykiss present (Fausch 2007;Britton et al 2010). In addition, the regulations on their releases into the wild in the countries are comparatively light compared with the species included in this study, with regulations concerning C. carpio and O. mykiss broadly similar to some native fishes.…”
Section: Non-native Fish Speciesmentioning
confidence: 99%
“…By contrast, the following non-native fishes were omitted from the study to avoid confounding issues with their heavy use in aquaculture would have potentially exposed them to a range of anti-parasite treatments: common carp Cyprinus carpio, goldfish Carassius auratus, rainbow trout Oncorhynchus mykiss and ide Leuciscus idus. Indeed, should any of these species be sampled in the wild in England and Wales then there is high probability they originated from a fish-farm as there are, for example, few naturally recruiting populations of C. carpio and O. mykiss present (Fausch 2007;Britton et al 2010). In addition, the regulations on their releases into the wild in the countries are comparatively light compared with the species included in this study, with regulations concerning C. carpio and O. mykiss broadly similar to some native fishes.…”
Section: Non-native Fish Speciesmentioning
confidence: 99%
“…A few studies have shown that impacts of IAS are higher in the environmental conditions for which they are adapted (e.g., oxygen concentration [MacNeil et al 2004]; salinity [Alcaraz et al 2008]; conductivity [Kestrup and Ricciardi 2009]). However, assessments of how climate change can affect the consumptive per capita impact of IAS are lacking in comparison to investigations of how abundance and area occupied will be affected (Parker et al 1999, Hellmann et al 2008 Peterson 2003, Bomford et al 2010, Britton et al 2010, to our knowledge no such procedure has been applied to impact; measurements of functional and physiological responses along environmental gradients could be useful predictors of the consumptive impacts of established IAS on native communities. Here, we provide the first general test of the Environmental Matching Hypothesis by conducting a meta-analysis of published data to examine the importance of temperature in determining IAS impact levels.…”
Section: Introductionmentioning
confidence: 99%
“…Such cold-water species may be vulnerable to the effects of warming temperatures caused by climate change (cf. Britton et al 2010;Hulme 2017). In some streams in Nova Scotia, the population density of brook trout was strongly related to water temperature, as streams that had a summer water temperature of 19 o C or more contained either few or no brook trout (MacMillan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of non-native species, no quantitative information is available regarding the consequences of such introductions (Simberloff et al 2013). Brook trout is classified as a medium-risk species among nonnative freshwater fish (Copp et al 2009;Britton et al 2010). Our article describes the distribution of brook trout in Norwegian water bodies.…”
Section: Methodsmentioning
confidence: 99%